Cyclosporine A regulates pro-inflammatory cytokine production in ulcerative colitis - Steiner, Stefanie; Daniel, Carolin; Fischer, Anika; Atreya, Imke; Hirschmann, Simon; Waldner, Maximilian; Neumann, Helmut; Neurath, Markus; Atreya, Raja; Weigmann, Benno (Archivum Immunologiae Et Therapiae Experimentalis, 2015)
Crohn's disease (CD) and ulcerative colitis (UC) are the two major forms of inflammatory bowel diseases (IBD), which are defined as relapsing inflammations of the gastrointestinal tract. Cyclosporine A (CsA) is a potential rescue treatment to avoid colectomy in severe steroid-refractory UC patients. The molecular mechanism of action of CsA in UC is nevertheless still not well understood. The aim of this study was to investigate the effect of CsA on a possible modulation of cytokine production by peripheral blood mononuclear cells (PBMCs) of controls and patients with UC or CD. Upon CsA treatment, analyses of cytokine levels revealed a significant reduction of IL-13 expression in PBMCs from patients with UC, whereas other cytokine expression levels remained unaffected. To address the question whether CsA treatment impinges on the induction of cell death, apoptosis assays were performed using CD4(+) T cells from peripheral blood of patients suffering from either UC or CD. It became clear that CsA treatment resulted in a specific induction of apoptosis in samples from controls and patients with UC but not with CD. Apoptosis induction was not mediated via the mitochondrial apoptosis pathway. The present data support the concept that CsA treatment modulates pro-inflammatory cytokine production and T cell survival in UC via the induction of apoptosis and might therefore help to explain the clinical efficacy of CsA in patients with UC.
EVALuna2:1844